TRANSFORMATIONS OF MEDIA PRACTICE IN ALGERIA WITHIN THE ELECTRONIC ENVIRONMENT AND EXECUTIVE DECREE NO. 20/332: A FIELD STUDY ON A SAMPLE OF ALGERIAN JOURNALISTS - Dalal Oulmi; Nadir Lamari; Khouloud Albekri Abdalkader (International Journal of Innovative Technologies in Social Science, 2025)
The objective of this study is to examine the reality of media practice in Algeria in light of Executive Decree No. 20/332, which regulates online media activity and the right of reply and correction, The issuance of this new decree comes at a time when the Algerian media landscape is witnessing intense debate over the increasing blocking of electronic news websites in recent months under various pretexts, while the government maintains that its intention is merely to regulate the sector rather than restrict freedoms. Based on this premise, the study adopts the descriptive survey method to explore the state of media practice under the decree from the perspective of a sample of Algerian journalists. The participants were selected using a simple random sampling technique to respond to a questionnaire specifically designed to achieve the study’s objectives.